Elevated Granzyme B in Cytotoxic Lymphocytes is a Signature of Immune Activation in Hemophagocytic Lymphohistiocytosis - Mellor-Heineke, Sabine; Villanueva, Joyce; Jordan, Michael B.; Marsh, Rebecca; Zhang, Kejian; Bleesing, Jack; Filipovich, Alexandra (Lisa) H.; Risma, Kimberly A. (Frontiers in Immunology, 2013)
Patients with hemophagocytic lymphohistiocytosis (HLH) exhibit immune hyper-activation as a consequence of genetic defects in secretory granule proteins of cytotoxic T lymphocytes (CTL) and natural killer (NK) cells. Murine models of HLH demonstrate significant activation of CTL as central to the disease pathogenesis, but evaluation of CTL and NK activation in children with HLH or inflammatory conditions is not well described. CD8 T cells only express granzyme B (GrB) following stimulation and differentiation into CTL; therefore, we reasoned that GrB expression may serve as a signature of CTL activation. It is unknown whether human NK cells are similarly activated in vivo, as marked by increased granule proteins. Perforin and GrB levels are measured in both CTL and NK cells by flow cytometry to diagnose perforin deficiency. We retrospectively compared GrB expression in blood samples from 130 children with clinically suspected and/or genetically defined HLH to age-matched controls. As predicted, CD8 expressing GrB cells were increased in HLH, regardless of genetic etiology. Remarkably, the GrB protein content also increased in NK cells in patients with HLH and decreased following immunosuppressive therapy. This suggests that in vivo activation of NK cells occurs in hyper-inflammatory conditions. We conclude that increased detection of GrB in CTL and NK are an immune signature for lymphocyte activation in HLH, irrespective of genetic subtype and may also be a useful measure of immune activation in other related conditions.